Case Report: Incarcerated femoral hernia containing ovary, unusual presentation of uncommon groin hernia - Priyank Gupta; Hadiel Kaiyasah; Mahra AlSuwaidi (CINQUILL Medical Publishers Inc., 2016)
Of all groin hernias, femoral hernias account for around 2-8%. They occur four to five times more commonly in females than males and have a peak incidence in those between 30 and 60 years old [1,2]. In adult population, femoral hernias are more commonly found in patients with previous inguinal hernia repair [3].